A Terminology Server for Medical Language and Medical Information Systems - Rector, A. L.; Solomon, W. D.; Nowlan, W. A.; Rush, T. W.; Zanstra, P. E.; Claassen, W. M. A. (Methods of Information in Medicine, 1995)
GALEN is developing a Terminology Server to support the development and integration of clinical systems through a range of key terminological services, built around a language-independent, re-usable, shared system of concepts – the CORE model. The focus is on supporting applications for medical records, clinical user interfaces and clinical information systems, but also includes systems for natural language understanding, clinical decision support, management of coding and classification schemes, and bibliographic retrieval. The Terminology Server integrates three modules: the Concept Module which implements the GRAIL formalism and manages the internal representation of concept entities, the Multilingual Module which manages the mapping of concept entities to natural language, and the Code Conversion Module which manages the mapping of concept entities to and from existing coding and classification schemes. The Terminology Server also provides external referencing to concept entities, coercion between data types, and makes its services available through a uniform applications programming interface. Taken together these services represent a new approach to the development of clinical systems and the sharing of medical knowledge.
Keywords: Terminology Server; Natural Language Processing; Coding and Classification; Electronic Medical Records; Knowledge Representation